Tata Niaga Garam Rakyat Dalam Kajian Struktural - Rochwulaningsih, Yety (Fakultas Ilmu Budaya, Universitas Diponegoro, 2013)
This article entitled Structural Studies of Community’s Salt Trade System studied the problems of how is the portrait of community’s salt trade system and the structural’s core problem which is created the chaotic trade system of community’s salt recently. The result shows that salt trade system tended to be out of the governments controll, so that it is thoroughly depended on the trade mechanism. Therefore, it become dominated and controlled commodity by capital owners in every level both locally and supra-locally and showed a hegemonic and monopolistic pattern. The capital owners got the maximum profit from salt commodity. In such condition, the salt farmer as the producer of salt raw materials had a very limited access and equity to the trade system. Ironically, government as the authoritical policy tended to preserve the trade structure. It was proven by the absence of decisive action and sanctions for trader that sent-up the salt’s price. Key words: trade system, community’s salt, structural, hegemonic, monopolistic.